2006
DOI: 10.1177/1471301206069929
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in dementia in perspective

Abstract: de men tia d e m e n t i aAbstract Many different definitions of the concept of quality of life (QOL) are found in the literature. This raises the question as to which domains are viewed as really important by people with dementia and which are possibly based on views of others, such as (in)formal carers, or theoretical models. An explorative study was carried out among people with dementia living in the community and in nursing homes. Their opinions were compared to those of professional carers and to the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(68 citation statements)
references
References 27 publications
3
59
0
6
Order By: Relevance
“…Another inevitable limitation of this study was the use of proxy reports to investigate residents' QoL. Dröes et al [28] found that there were differences in the perspectives on QoL between people with dementia and their caregivers. Also, the younger age of our residents could have influenced the proxy reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another inevitable limitation of this study was the use of proxy reports to investigate residents' QoL. Dröes et al [28] found that there were differences in the perspectives on QoL between people with dementia and their caregivers. Also, the younger age of our residents could have influenced the proxy reports.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in current research on YOD, unclear definitions of the concept of QoL are used, and therefore it is uncertain which specific aspects of QoL were measured [26] . The multidimensionality of the QoL construct stresses the importance of investigating QoL domains separately to provide clarity regarding the possible differences in specific QoL domains and thereby prevent a loss of information [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown, however, that residents with dementia still consider occupation to be important for their quality of life (Train et al, 2005;Dröes et al, 2006). Moreover, several studies show that occupation can have beneficial effects on the wellbeing of long-term care residents with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors argue that social demographic factors are related to quality of life [29,30]. However, a review paper concluded that neither age, gender nor education was associated with a lower quality of life in persons with dementia [31].…”
Section: Introductionmentioning
confidence: 99%